Organizational flexibility estimation - Komarynets, Sofia (Видавництво Львівської політехніки, 2013)
By the help of parametric estimation the evaluation scale of organizational flexibility and its parameters was formed. Definite degrees of organizational flexibility and its parameters for the Lviv region enterprises were determined. Grouping of the enterprises under the existing scale was carried out. Special recommendations to correct the enterprises behaviour were given.
Keywords: organizational flexibility; organizational flexibility estimation; the evaluation scale of organizational flexibility; organizational flexibility parameters; parametric estimation method of organizational flexibility